14 St2 levels are elevated in patients with advanced heart failure but are not consistently associated with other markers of adverse prognosis. (5th June 2017) - Kankam, Hadyn; Kirk, Nick; Fitzsimons, Sarah; Pettit, Stephen
Abstract : Introduction: Heart transplantation and mechanical circulatory support (MCS) improve survival in selected patients with advanced heart failure and an adverse prognosis. Soluble ST2 is a protein belonging to the interleukin-1 receptor family. ST2 is released in response to cardiomyocyte stess and thought to be a marker of adverse prognosis. We examined the association between ST2 levels and currently accepted markers of adverse prognosis in patients with advanced heart failure. Methods: We included 20 consecutive outpatients who were assessed for heart transplantation at Papworth Hospital over ten weeks. All patients underwent echocardiography, six minute walk testing, cardiopulmonary exercise testing and right heart catheterisation, in addition to blood tests including serum ST2 measurement using a commercial assay. Prognosis was estimated using the Seattle Heart Failure Model (SHFM) and the Meta-Analysis Global Group in Chronic Heart Failure (MAGGIC) scores. A multi-disciplinary team decided whether listing for heart transplantation was indicated. We examined the association between ST2 levels and other markers of adverse prognosis. Results: Ten patients were too well to be listed for heart transplantation (group A) and ten patients were sufficiently unwell to be listed for heart transplantation (group B). There was no difference in age, gender or body mass index. Key prognostic variables are presented in table 1. Compared with patients in group A, patients in group B had higher ST2 levels, lower peak VO2, shorter six minute walk distance and higher SHFM predicted one-year mortality. However, there was no difference in LVEF, serum Creatinine, NTproBNP, cardiac index or predicted one-year mortality by MAGGIC score. Previous studies have found that an ST2 level of >35 ng/ml is indicative of adverse prognosis. At this cut-off, there was frequent disagreement between ST2 level and other markers of adverse prognosis. Patients identified as high risk by ST2 level were identified as low risk by peak VO2 (n=5) and six minute walk distance (n=6). In addition, eight patients identified as low risk by ST2 level were identified as high risk by NTproBNP (figure 1). Conclusions: ST2 levels are higher in patients who are sufficiently unwell to be listed for heart transplantation, compared with those who are too well to be listed for heart transplantation. However, there is frequent disagreement between ST2 levels and other markers of adverse prognosis such as six minute walk distance, peak VO2 and NTproBNP. Larger studies with assessment of real world outcomes, such as death, urgent heart transplantation or MCS, are required to determine whether ST2 measurement can improve assessment of prognosis in patients with advanced heart failure.